Three-dimensional kinematics of the pelvis and hind limbs in chimpanzee (Pan troglodytes) and human bipedal walking. Issue 86 (September 2015) - O'Neill, Matthew C.; Lee, Leng-Feng; Demes, Brigitte; Thompson, Nathan E.; Larson, Susan G.; Stern, Jack T.; Umberger, Brian R.
Abstract: The common chimpanzee ( Pan troglodytes ) is a facultative biped and our closest living relative. As such, the musculoskeletal anatomies of their pelvis and hind limbs have long provided a comparative context for studies of human and fossil hominin locomotion. Yet, how the chimpanzee pelvis and hind limb actually move during bipedal walking is still not well defined. Here, we describe the three-dimensional (3-D) kinematics of the pelvis, hip, knee and ankle during bipedal walking and compare those values to humans walking at the same dimensionless and dimensional velocities. The stride-to-stride and intraspecific variations in 3-D kinematics were calculated using the adjusted coefficient of multiple correlation. Our results indicate that humans walk with a more stable pelvis than chimpanzees, especially in tilt and rotation. Both species exhibit similar magnitudes of pelvis list, but with segment motion that is opposite in phasing. In the hind limb, chimpanzees walk with a more flexed and abducted limb posture, and substantially exceed humans in the magnitude of hip rotation during a stride. The average stride-to-stride variation in joint and segment motion was greater in chimpanzees than humans, while the intraspecific variation was similar on average. These results demonstrate substantial differences between human and chimpanzee bipedal walking, in both the sagittal and non-sagittal planes. These new 3-D kinematic data are fundamental to a comprehensive understanding of the mechanics, energetics and control of chimpanzee bipedalism.